Androgen therapy in inherited bone marrow failure syndromes: analysis from the Canadian Inherited Marrow Failure Registry. (3rd March 2020) - Català, Albert; Ali, Salah S.; Cuvelier, Geoffrey D. E.; Steele, MacGregor; Klaassen, Robert J.; Fernandez, Conrad V.; Pastore, Yves D.; Abish, Sharon; Rayar, Meera; Jardine, Lawrence; Breakey, Vicky R.; Brossard, Josee; et al.
Summary: Progressive cytopenia is a serious complication among paediatric patients with inherited bone marrow failure syndromes (IBMFS). Androgens have been used to improve blood counts in different bone marrow failure conditions. Little is known about efficacy and toxicity with new androgens (i.e., danazol) in different types of IBMFS. We identified 29 patients from the Canadian Inherited Marrow Failure Registry, who received oxymetholone or danazol. Sixteen (55%) had haematological response including patients with unclassified IBMFS (45%). Danazol showed a better toxicity profile and similar efficacy compared to oxymetholone. Androgens are an effective and safe option to ameliorate bone marrow failure in IBMFS.